AN ANALYSIS OF FILLERS USED BY LECTURER AND STUDENTS IN EFL CLASSROOM INTERACTION - Gotin Siti Fatimah (JALL (Journal of Applied Linguistics and Literacy), 2017)
This paper reports on how fillers are used by lecturer and students in EFL Classroom Interaction. Therefore, the study was aimed to investigate the types and frequency of the lecturer and the students’ fillers and the functions of fillers in EFL Classroom Interaction. A qualitative case study was obtained through the observation. Then, the data from the observations were analyzed by transcribing the whole of the utterances that contained fillers to find out the types, frequency and functions of fillers. The data from observation was described qualitatively. In the present study, the writer proposed two research questions: (1) Which types of lexicalized and unlexicalized fillers will be used and how often do the lecturer and the students use both fillers in EFL Classroom Interaction? (2) What are the functions of lexicalized and unlexicalized fillers used by the lecturer and the students in EFL Classroom Interaction? In responding to the first research questions, It was found that the lecturer  and the students used filler in their utterances, the fillers  found were both lexicalized and unlexicalized fillers. The lecturer used 504 fillers, while the students used 65 fillers. Furthermore, the result of second research question also found. The highest percentage of the fillers’ function of the lecturer and the students reached the same range used as a mark hesitation : (28.91%) for the lecturer and (77.5%) for the students.Keyword: Discourse Markers, Fillers, Classroom Interaction